2014
DOI: 10.1186/1471-2121-15-23
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin expression in Trypanosoma cruzi

Abstract: BackgroundClathrin-mediated vesicular trafficking, the mechanism by which proteins and lipids are transported between membrane-bound organelles, accounts for a large proportion of import from the plasma membrane (endocytosis) and transport from the trans-Golgi network towards the endosomal system. Clathrin-mediated events are still poorly understood in the protozoan Trypanosoma cruzi, the causative agent of Chagas disease in Latin America. In this study, clathrin heavy (TcCHC) and light (TcCLC) chain gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…These studies highlighted the broad specificity of the SPC by showing that it was capable of shuttling BSA, IgG, Transferrin, and CFSE labeled host protein through this endocytic pathway. Surprisingly, we failed to observe any endocytosis of cargo, including albumin (BSA), via the flagellar pocket in our assays suggesting that the SPC may be the exclusive endocytic route for whole protein uptake in this parasite (Soares and de Souza, 1991;de Figueiredo and Soares, 2000;Kalb et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…These studies highlighted the broad specificity of the SPC by showing that it was capable of shuttling BSA, IgG, Transferrin, and CFSE labeled host protein through this endocytic pathway. Surprisingly, we failed to observe any endocytosis of cargo, including albumin (BSA), via the flagellar pocket in our assays suggesting that the SPC may be the exclusive endocytic route for whole protein uptake in this parasite (Soares and de Souza, 1991;de Figueiredo and Soares, 2000;Kalb et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
“…It is notable that we only observed endocytosis via the SPC and failed to detect protein uptake through the flagellar pocket. This is in stark contrast to T. brucei which endocytoses exclusively through its flagellar pocket and to previously published reports of T. cruzi (de Figueiredo and Soares, 2000;Kalb et al, 2014). In order to evaluate endocytosis in intracellular amastigotes, we stained host cells first with the free-amine labeling fluorescent dye CFSE followed by infection with trypomastigotes from the CP1-Ty tagged line.…”
Section: Cp1 Labels the Protein Endocytic Pathway Of The Cytostome-cymentioning
confidence: 95%
See 1 more Smart Citation
“…Two different tracers were used: transferrin (mostly internalized via the cytostome) and albumin [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that this parasite has clathrin that could participate in endocytosis [ 54 , 55 ], morphological studies have demonstrated that Tf internalization is carried out through a clathrin-independent and cholesterol-dependent endocytosis pathway. This pathway was identified by the utilization of specific inhibitors of endocytic pathways.…”
Section: Tfr In Protozoan Parasitic Organismsmentioning
confidence: 99%